Konstruksi Mutu Penyelenggaraan Pendidikan Raudhatul Athfal di Kartasura - Fetty Ernawati (BUANA GENDER : Jurnal Studi Gender dan Anak, 2016)
The main problem in this study was the increased number of students who enrolled education in Raudhatul Athfal (RA) was not corresponded to the improved quality of institution management. This study aims to obtain the description of education management quality in RA and to construct its management quality. The quality is perceived from the stakeholder’s perception, needs, and wants. This study is a quantitative one. The data collection used questionnaire which is developed based on the standard of early childhood education, known as PAUD, in the Regulation of Minister of Education and Culture No. 137 of 2014 and was performed on 7 RA/BA in Kartasura, Sukoharjo, which have the establishments operating licenses. The research result showed that, 1) the implemented RA management referred to PAUD standard in the regulation. The quality problem was found in the quality of educators and educational staff, as well as facilities and infrastructures; 2) the construction of RA management quality was consistent with PAUD standard in the regulation and it was inseparable from the institutions ability to perform strategic and quality management.Problem utama dalam penelitian ini adalah peningkatan jumlah siswa yang mengikuti pendidikan di Raudhatul Athfal kurang diimbangi peningkatan mutu pengelolaan lembaga Raudhatul Athfal. Penelitian ini bertujuan untuk memperoleh gambaran mutu penyelenggaraan pendidikan Raudhatul Athfal dan mengkonstruksi mutu penyelenggaraan Raudhatul Athfal. Mutu dilihat dari persepsi stakeholder, dan kebutuhan serta kemauan stakeholder. Penelitian ini merupakan penelitian kuantitatif. Pengambilan data menggunakan angket yang dikembangkan berdasarkan standar PAUD yang tercantum dalam Permendikbud Nomer 137 tahun 2014 dan dilakukan pada 7 RA/BA di wilayah Kartasura, Sukoharjo yang telah memiliki ijin operasional pendirian. Hasil penelitian menunjukkan bahwa, 1) penyelenggaraan RA yang telah  dilakukan mengacu pada standar PAUD dalam Permendikbud Nomer 137 Tahun 2014. Permasalahan mutu terletak pada mutu pendidik dan tenaga kependidikan serta sarana prasarana; 2) konstruksi mutu penyelenggaraan RA adalah penyelenggaraan RA sesuai dengan standar PAUD dalam Permendikbud Nomer 137 Tahun 2014 dan mutu penyelenggaraan RA tidak terlepas dari kemampuan lembaga melakukan manajemen strategik dan manajemen mutu.